Labor Costs in the United States Compared with Costs Elsewhere - Taussig, F. W. (Quarterly Journal of Economics, 1924)
The comparison is of labor costs in the sense of quantity of labor per unit of output. — I. Coal in the United States and other countries, 98. — II. The United States and Great Britain: iron and steel; other articles, 102. — III. Window-glass in the United States, Belgium, and Sweden, 107. — IV. Cotton goods in the United States and Japan, 111.